Sharing economy jako nowy trend konsumencki - Ziobrowska, Justyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
New technologies are responsible for fast changing of the global economy. Together with mobile internet and gains of trust in the courageous start-ups there is a new branch of economy developing – the sharing economy. We are becoming participants of the economic revolution, which changes the current understanding of consumption and laws of ownership. It is the time, when anaccess to services and things creates a new form and expands classic atributes of owner ship eligibility. The goal of this article is to show the concept and possible applications of the sharing economy. The Author describes definitions, points to advantages and disadvantages of the common consumption and examples of the companies which base their strategy on the sharing economy. In the article there has been used a method of literature analysis and document research.
Keywords: sharing economy; ownership